ANALYSIS AND DESIGN OF USER INTERFACE (UI) AND USER EXPERIENCE (UX) ON THE UIN AR-RANIRY SPORT CENTER BUILDING ORDERING WEBSITE USING THE USER CENTERED DESIGN METHOD - Usman, Himawan; Ridwan, Ridwan; Islamadina, Raihan (Barkah Publishing, 2025)
The research aims to create a website system at the UIN Ar-Raniry sports center building, in order to make it easier for customers to access information about available field schedules. The goal is to create a UI/UX prototype of the web so that it suits the user, and test the web prototype so that it can be said to be suitable for use. The web prototype design method uses User Centered Design (UCD) and tests the feasibility of the prototype using the System Usability Scale (SUS). In the development stage, involving users to design web components to suit user needs. The web feasibility test used the SUS questionnaire which was distributed via Google Form to 20 respondents, namely 1 manager, 2 employees and 17 customers. The results of this test obtained a final SUS scale score of 81.12. Based on these results, it can be concluded that the prototype can be used and meets user needs, because the final SUS score is in the